2014
DOI: 10.3109/0886022x.2013.872570
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status in stage V dialyzed patient versus CKD patient on conservative therapy across different economic status

Abstract: Several nutritional parameters were below the recommended international guidelines for all the three groups, though the high income group had better parameters from several indicators. There is an urgent need for nutritional counseling for CKD-D and CKD-ND patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Malnutrition has been widely reported in Indian patients on dialysis. 5,6 Malnutrition in CKD is associated with increased morbidity, mortality and poor quality of life. 7,8 However, there is a paucity of multicentric longitudinal data on hydration and nutritional status of Indian dialysis patients and its effect on all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition has been widely reported in Indian patients on dialysis. 5,6 Malnutrition in CKD is associated with increased morbidity, mortality and poor quality of life. 7,8 However, there is a paucity of multicentric longitudinal data on hydration and nutritional status of Indian dialysis patients and its effect on all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Anthropometric measures and serum albumin in the present study were similar to those reported in another Indian study evaluating nutritional status among CKD patients. [ 28 ] In the present study, though not statistically significant, delayed GE group had poorer nutrition (as suggested by lower anthropometric measures and serum albumin) compared to the rest [Tables 4 and 5 ]. Similar findings of more severe malnutrition among CKD patients with delayed GE have been reported in earlier studies.…”
Section: Discussionmentioning
confidence: 48%
“…The number of AVF creation and patients going for dialysis even in ER groups remained minuscule compared recommended reference [ 17 ]. A majority do not opt for any modality of RRT, only a few renal transplantations, and the high death rate suggests no improvement in CKD care and management over the decades [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hypocalcemia, high phosphorus, and increased alkaline phosphatase have increased mortality, indicating nonoptimized care for CKD. The low serum albumin, cholesterol, and triglyceride level indicate the poor nutritional status of the patients who died [ 20 ]. It also indicates that many of these patients did not receive appropriate supportive care before referral, either due to late diagnosis or due to late referral.…”
Section: Discussionmentioning
confidence: 99%